Outcomes of and Satisfaction with the Inflatable Penile Prosthesis in the Elderly Male. (29th May 2012) - Villarreal, Humberto G.; Jones, LeRoy
Abstract : Objective . To determine the outcomes of and satisfaction with the multi-component inflatable penile prosthesis (IPP) in the elderly male (age >71). Methods . Using a chart review and telephone survey, we retrospectively assessed patients who underwent IPP or combined IPP/artificial urinary sphincter (AUS) from 2004–2006. Results . We identified 56 patients that underwent IPP (48) or IPP/AUS (8). The age range was 71–86 (mean 74.3) at the time of surgery, with a follow-up range of 0.5–2.4 years (mean 1.5). The overall complication rate was 3.8% (2 of 56) with one device removed for infection and a second patient requiring exploration for a postoperative hematoma. The telephone interview was conducted with 35 of 56 patients. Patients rated ease of use (a scale from 1–5, 5 meaning very easy) and overall satisfaction (a scale of 1–5, 5 meaning very satisfied) at an average of 4.1 and 4.3, respectively. IPP usage varied from 0–7 times per month (mean 3.3). 32 of 35 patients (91%) said they would undergo the procedure again. Conclusion . Our review demonstrates that the IPP is well tolerated in the elderly male population, who report a high degree of satisfaction and ease of use with this device.